Development of an automatable micro-PCC biodosimetry assay for rapid individualized risk assessment in large-scale radiological emergencies - Pantelias, Antonio (Mutat Res, 2018)
In radiation accidents and large-scale radiological emergencies, a fast and reliable triage of individuals according to their degree of exposure is important for accident management and identification of those who need medical assistance. In this work, the applicability of cell-fusion-mediated premature chromosome condensation (PCC) in G(0)-lymphocytes is examined for the development of a rapid, minimally invasive and automatable micro-PCC assay, which requires blood volumes of only 100μl and can be performed in 96-well plates, towards risk assessments and categorization of individuals based on dose estimates. Chromosomal aberrations are visualized for dose-estimation analysis within two hours, without the need of blood culturing for two days, as required by conventional cytogenetics. The various steps of the standard-PCC procedure were adapted and, for the first time, lymphocytes in blood volumes of 100μl were successfully fused with CHO-mitotics in 96-well plates of 2ml/well. The plates are advantageous for high-throughput analysis since the various steps required are applied to all 96-wells simultaneously. Interestingly, the use of only 1.5ml hypotonic and Carnoy’s fixative per well offers high quality PCC-images, and the morphology of lymphocyte PCCs is identical to that obtained using the conventional PCC-assay, which requires much larger blood volumes and 15ml tubes. For dose assessments, appropriate calibration curves were constructed and for PCC analysis specialized software (MetaSystems) was used. The micro-PCC assay can be combined with fluorescence in situ hybridization (FISH), using simultaneously centromeric/telomeric (C/T) peptide nucleic acid (PNA) probes. This allows dose assessments on the basis of accurate scoring of dicentric and centric ring chromosomes in G(0)-lymphocyte PCCs, which is particularly helpful when further evaluation into treatment-level categories of exposed individuals is needed. The micro-PCC assay has significant advantages for early triage biodosimetry when compared to other cytogenetic biodosimetry assays. It is rapid, cost-effective, and could pave the way to its subsequent automation.